2004
DOI: 10.1021/jf049144d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Antioxidant and Chemopreventive Ellagitannins from Strawberries, Raspberries, Walnuts, and Oak-Aged Wine in Humans:  Identification of Biomarkers and Individual Variability

Abstract: Ellagitannins (ETs) are dietary polyphenols, containing ellagic acid (EA) subunits, with antioxidant and cancer chemopreventive activities that might contribute to health benefits in humans. However, little is known about their metabolic fate. We investigate here the metabolism of different dietary ETs and EA derivatives in humans. Forty healthy volunteers were distributed in four groups. Each group consumed, in a single dose, a different ET-containing foodstuff, i.e., strawberries (250 g), red raspberries (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
388
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(427 citation statements)
references
References 40 publications
33
388
2
4
Order By: Relevance
“…A high individual variability was observed in the metabolism of PJ by COPD patients along the trial (results not shown). This was supported by previous reports regarding the metabolism of ellagitannins by humans (Cerdá et al, 2005) and by the no relationship between metabolism of PJ polyphenols and the diet histories provided by the patients (results not shown). At the end of the 5-week intervention period, a mean concentration of the above metabolites, 2.0171.6 and 2.472.3 mg/ml, respectively, was detected in urine.…”
Section: Resultssupporting
confidence: 89%
“…A high individual variability was observed in the metabolism of PJ by COPD patients along the trial (results not shown). This was supported by previous reports regarding the metabolism of ellagitannins by humans (Cerdá et al, 2005) and by the no relationship between metabolism of PJ polyphenols and the diet histories provided by the patients (results not shown). At the end of the 5-week intervention period, a mean concentration of the above metabolites, 2.0171.6 and 2.472.3 mg/ml, respectively, was detected in urine.…”
Section: Resultssupporting
confidence: 89%
“…Our results show that G. rivale and G. urbanum are rich sources of EA, but mostly in the bound form. As hydrolyzable tannins easily undergo hydrolysis in the gastrointestinal tract (Clifford and Scalbert, 2000;Cerdá et al, 2005), its actual bioavailability could be quite substantial. EA is an important natural compound whose potent antioxidant properties may be benefi- (Khanduja et al, 1999;Hwang et al, 2010;Kannan and Quine, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…EA and GA can exist in plant material in free form but the main sources of these compounds are hydrolyzable tannins (ellagitannins and gallotannins), which upon hydrolysis release a sugar and a respective acid moiety (Haslam, 2007;Serrano et al, 2009). Hydrolytic degradation of hydrolyzable tannins can occur in the gastrointestinal tract after ingestion of the medicine (Clifford and Scalbert, 2000;Cerdá et al, 2005). EA and GA, as the major products of hydrolyzable tannin degradation, might therefore have a significant effect on the activity of herbal remedies containing large amounts of hydrolyzable tannins.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UA was studied in detail, since prior studies demonstrated that UA conjugates were the most prevalent metabolites of EA in human subjects and that they persist for up to 56 h after ingestion of ETs (9,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, urolithins appear in blood, urine, and feces of human volunteers 12-24 h after consumption of a single dose of several ET-rich foods and persist in vivo for up to 48-56 h after ingestion (9)(10)(11)(12). Despite these advances in understanding ET metabolism in rodents (13,14) and humans (9-12), there have been no studies determining the disposition of ET metabolites to tissues of interest including the prostate.…”
Section: Introductionmentioning
confidence: 99%